Performa Kompor Gasifikasi Champion Stove - Retna Julita; David Andrio; Hari Rionaldo; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Energy requirements for household cooking needs still depend on LPG (Liquefied Petroleum Gas). However, the lack of LPG supply and poor distribution are still obstacles in the community. Biomass waste is one of the alternative fuels for society so that cooking energy needs can be met. The objective of research is to study the effect of type of biomass and biomass size on the performance of gasification stoves by using a water boiling test (WBT) analysis. The experiments were carried out in batches with two WBT phases, namely cold start and hot start. The first stage was a cold start, where the tester uses a stove at room temperature an a number of fuels to boil 2.5 liters of water in a standard pan. The second stage was called the hot start test, where water is boiled with a hot stove with the aim of identifying the difference in the stove’s power when it’s cold and when it’s hot. In addition, the flame temperature and stove operating time are the performance parameters of the stove champion gasification stove. Water content for each biomass used is between 10-13%. The resulting flame color is reddish yellow with a fire height of 30-72 cm. The maximum flame temperature produced by the stove is 806,3 oC using mahogany wood. Key words: biomass gasification, gasification stove, water boiling test (WBT).